2016
DOI: 10.1002/smll.201600053
|View full text |Cite
|
Sign up to set email alerts
|

Boron Nitride Nanostructures: Fabrication, Functionalization and Applications

Abstract: Boron nitride (BN) structures are featured by their excellent thermal and chemical stability and unique electronic and optical properties. However, the lack of controlled synthesis of quality samples and the electrically insulating property largely prevent realizing the full potential of BN nanostructures. A comprehensive overview of the current status of the synthesis of two-dimensional hexagonal BN sheets, three dimensional porous hexagonal BN materials and BN-involved heterostructures is provided, highlight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
165
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 213 publications
(168 citation statements)
references
References 296 publications
(437 reference statements)
3
165
0
Order By: Relevance
“…For carbon nanotubes, semiconducting or metallic tubes are possible depending on a tube’s bonding topology. Boron-nitride nanotubes [15] and other nanotubes have been fabricated and studied. Moreover, wires with nanometer scale diameters have also been grown using Si [16], Se [17] and GaAsSb [18], to name a few.…”
Section: Introductionmentioning
confidence: 99%
“…For carbon nanotubes, semiconducting or metallic tubes are possible depending on a tube’s bonding topology. Boron-nitride nanotubes [15] and other nanotubes have been fabricated and studied. Moreover, wires with nanometer scale diameters have also been grown using Si [16], Se [17] and GaAsSb [18], to name a few.…”
Section: Introductionmentioning
confidence: 99%
“…[2,[8][9][10] To date,H ermans et al reported that bulk h-BN and boron nitride nanotubes (BNNT) exhibited unique and highly efficient catalytic properties for the oxidative dehydrogenation of propane,resulting in great selectivity to olefins (79 % propene and 12 %e thene at 14 %p ropane conversion). [14,15] Our group previously presented an efficient strategy for the scalable synthesis of few-layered h-BNNS using agas exfoliation of bulk h-BN in liquid N 2 . Thet hickness of the h-BN materials (bulk vs.f ew layered) also had asignificant effect on their properties.Generally,few layered h-BNNS are preferred, which are mostly prepared via either as olid-phase mechanical method [13] or liquid-phase exfoliation.…”
mentioning
confidence: 99%
“…Thet hickness of the h-BN materials (bulk vs.f ew layered) also had asignificant effect on their properties.Generally,few layered h-BNNS are preferred, which are mostly prepared via either as olid-phase mechanical method [13] or liquid-phase exfoliation. [15,17] Compared with amorphous materials,t heir highly crystalline counterparts have ordered structures and fewer defects,t hus leading to enhanced performance in optoelectronics and catalysis, [18] as shown by the significant development of crystalline metalorganic framework (MOF) nanosheets, [19] and 2D covalent organic frameworks (COFs). [16] However, the final few-layered h-BNNS obtained through these approaches often suffer from low surface areas or amorphous/low crystalline structures.…”
mentioning
confidence: 99%
See 2 more Smart Citations